Management of Pregnancy in 31-Year-Old Woman with Persistent Atrial Flutter After Cone Reconstruction for Ebstein’s Anomaly - Eliana Susilowati (Universitas Airlangga, 2020)
There is a growing number of mothers suffering innate heart disease which could potentially risk their gestation period. Ebstein’s anomaly refers to a rare innate disease in the heart which accounts for less than 1% of most cases of innate heart disease, and only 5% of the patients surviving beyond 50 years of age. Cone reconstruction (CR) is an option for the repairment of tricuspid valve in patients with Ebstein anomaly. However, persistent arrhytmia, such as AFL, is possible to occur after CR. This case report aims to opt suitable pregnancy management of patients with persistent atrial flutter (AFL) after Cone reconstruction for Ebstein’s Anomaly. We report a 31 year-old woman who consulted for pregnancy planning due to history of Ebstein’s Anomaly, and had undergone successful cone reconstruction. No recorded history of AFL is reported. Physical examination finding was tricuspid regurgitation murmur without signs and symptoms of right ventricular failure. Electrocardiography showed counter-clockwise typical AFL. Echocardiography finding demonstrated post Cone reconstruction (CR), mild tricuspid regurgitation, and EF of 76%.